2023
DOI: 10.1007/s10597-022-01086-7
|View full text |Cite
|
Sign up to set email alerts
|

Sociodemographic Characteristics and Patterns of Suicide in Pakistan: An Analysis of Current Trends

Abstract: Suicide is a global phenomenon with about 79% of suicides occurring in low and middle-income countries. This study investigated current trends, demographics, and characteristics of completed suicides based on reports from leading Pakistani Newspapers. This study performed a qualitative analysis of completed suicides in Pakistan's four newspapers from January 1st, 2019, through December 31st, 2020. Data about socio-demographic characteristics, methods of suicide, possible motives, and associated features were a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 19 publications
0
5
0
Order By: Relevance
“…11 Pakistan and Bangladesh are neighboring countries with high population density. Both these countries are passing through demographic transition where bulk of population is in young age group 6 which is also emotionally unstable, hence high burden of suicidal deaths in young age group can be attributed to this feature. In our study 81.7% of suicidal cases were males, which is another important finding.…”
Section: Sample Sizementioning
confidence: 99%
See 1 more Smart Citation
“…11 Pakistan and Bangladesh are neighboring countries with high population density. Both these countries are passing through demographic transition where bulk of population is in young age group 6 which is also emotionally unstable, hence high burden of suicidal deaths in young age group can be attributed to this feature. In our study 81.7% of suicidal cases were males, which is another important finding.…”
Section: Sample Sizementioning
confidence: 99%
“…A recently published study revealed that 2295 suicides were reported during a two-year period (2019,2020) in Pakistan. 6 Suicide is an extremely unfortunate event with multifaceted roots. The probable causes include physical and mental illnesses, disturbed relations, economic crises.…”
Section: Introductionmentioning
confidence: 99%
“…Due to fear of societal stigma and legal issues, families withhold information about assault and self-harm and label it as accidental. This cany lead to misclassification and undercounting of cases 9 10…”
Section: Introductionmentioning
confidence: 99%
“…Suicide is a serious global public health issue ( Cheng et al, 2020 ; World Health Organization, 2021a ; Canbolat and Gençöz, 2023 ; Imran et al, 2023 ; Naveed et al, 2023 ). Every suicide is a tragedy that affects families, communities, and entire countries ( Bengesser et al, 2000 ; World Health Organization, 2021b ) and has long-lasting effects on the people left behind ( Cain, 2002 ; Avrami, 2003 ; Mintz-Binder, 2007 ; Rosenberg, 2017 ; Vidal-Ribas et al, 2021 ; Connell et al, 2022 ).…”
Section: Introductionmentioning
confidence: 99%